Smartirrigation Apps: Urban Turf - Kati W. Migliaccio; J. H. Debastiani Andreis; Clyde Fraisse; Kelly T. Morgan; G. Vellidis (EDIS, 2013)
We developed an app called Smartirrigation Turf to provide an easy-to-use mobile tool that delivers information to improve irrigation scheduling for urban turf. Using the app instead of a set time-based schedule for irrigation, homeowners and others can provide irrigation amounts to turf that more closely match water needs. This version of the app is applicable in Florida and Georgia and is available to download in the Apple App Store and Google Play Store. This 5-page fact sheet was written by K. W. Migliaccio, J. H. Debastiani Andreis, C. Fraisse, K. T. Morgan, and G. Vellidis, and published by the UF Department of Agricultural and Biological Engineering, October 2013.